IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU (STUDI RETRIBUSI PELAYANAN PASAR TAHUN 2014 PADA PASAR CIK PUAN KOTA PEKANBARU) - Jumaiti "; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In order for an activity or market activity running smoothly then Pekanbaru City Government also issued a policy through a Regional Regulation Pekanbaru No. 6 of 2012 on Service Fees Market. Retribution market development efforts in each year with obstacles or barriers. Among them are obstacles or barriers concerning the behavior compulsory levy, the compulsory levy arrears payments market often do levy a variety of reasons. Receipt of arrears is then obtained can not be optimal. The problem of this study is what factors are influencing and any obstacles encountered in the implementation of Regional Regulation Pekanbaru (Study levy service market in 2014 at Cik Puan Pekanbaru City Market).The study authors do in Pekanbaru City Market Agency, the reason is because the choice of location less optimal symptom of Cik Puan market fee collection Pekanbaru, levy income earned is not in accordance with the target. The research is a qualitative descriptive method. This research using key informants as a source of information by using some interview questions to obtain research data is needed.Namely the implementation of research results Pekanbaru City Regional Regulation (Study 2014 Market Service Fees On The Market Cik Puan Pekanbaru City) in the category quite well. The obstacles encountered in the implementation of Sub Office Market local government policy in market fee collection in the city of Pekanbaru is a lack of awareness in the levy shall pay the levy markets, market infrastructure inadequate and officers less assertive in collecting levies.